Effects of Cupping Therapy on Range of Motion: A Study on Healthy High School Athletes - Mr Parth Parmar (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Purpose: The purpose of this study was to assess the effects of cupping therapy and passive stretching on shoulder internal and external rotation in healthy male high school athletes. Methods: Participants included nine high school male football players recruited from a local private high school. An eight-minute cupping therapy treatment was completed on one arm, while passive shoulder stretching was completed on the other. Pre and post-intervention measurements were taken for shoulder internal and external rotation and analyzed. Results: Analysis revealed that shoulder internal rotation range of motion post-intervention was significantly higher than at pre-intervention (p = 0.003). However, there was no significant difference between shoulder internal rotation in the cupping therapy group and the passive stretching group (p = 0.879). Similarly, shoulder external rotation range of motion post-intervention was significantly higher than at pre-intervention (p = 0.021), but there was no significant difference between the cupping therapy group and passive stretching group (p = 0.621). Conclusions: The results of this study conclude that cupping therapy treatment was as effective as passive stretching treatment at increasing shoulder internal and external rotation in healthy high school males. Application in Sports: Cupping therapy is widely used by clinicians and athletes for a variety of reasons. Although this study did not find that cupping therapy is superior to passive stretching in healthy high school-aged males, it demonstrated that this intervention is as effective as passive stretching and provides the clinician with an additional method of treatment.